2011
DOI: 10.4018/jabim.2011040103
|View full text |Cite
|
Sign up to set email alerts
|

Financial Reporting of Intellectual Capital and Company’s Performance in Indian Information Technology Industry

Abstract: This paper examines the relationship between Financial Reporting of Intellectual Capital and Company’s Performances in Indian Information Technology Industry. For the purpose of this study, sixty companies listed on NSE were taken for a period of 1999-00 to 2008-09. Value Added Intellectual Co-efficient (VAICTM) method developed by Pulic (1998) was used for the analysis of the data. The present study uses VAICTM model and regression equation for the evaluation of intellectual capital and their relationship wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Ten long years after the UNCTAD report, the current study found the same underutilisation scenario for IC management in Bangladeshi textile sector. This research outcome is consistent with previous studies on emerging economies (Deep and Narwal, 2014; Dzenopoljac et al , 2017; Firer and Williams, 2003; Khanqah et al , 2012; Pal and Soriya, 2012), in which IC was found to play a minimal role to play in predicting superior financial outcomes. Deep and Narwal (2014) demonstrated a significant and positive influence of VAIC components on profitability and no effect on productivity ratio in the Indian textile industry.…”
Section: Conclusion and Direction For Future Studiessupporting
confidence: 91%
See 2 more Smart Citations
“…Ten long years after the UNCTAD report, the current study found the same underutilisation scenario for IC management in Bangladeshi textile sector. This research outcome is consistent with previous studies on emerging economies (Deep and Narwal, 2014; Dzenopoljac et al , 2017; Firer and Williams, 2003; Khanqah et al , 2012; Pal and Soriya, 2012), in which IC was found to play a minimal role to play in predicting superior financial outcomes. Deep and Narwal (2014) demonstrated a significant and positive influence of VAIC components on profitability and no effect on productivity ratio in the Indian textile industry.…”
Section: Conclusion and Direction For Future Studiessupporting
confidence: 91%
“…This result was consistent with later studies by Pal and Soriya (2011); Shaban and Kavida (2013) and Vishnu and Kumar Gupta (2014) in the context of Indian IT industry and pharmaceutical firms. Pal and Soriya (2012) performed a comparative study on the Indian pharmaceutical and textile industries to suggest a positive influence of IC on profitability, but found no significant link between ICE and productivity. Firer and Williams (2003) and Dzenopoljac et al (2017) described limited and mixed outcomes for the association of IC and financial performance in South Africa and the Arab region, respectively, where corporate performance is influenced mostly by physical assets.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation